Risk Factors and Spatial Distribution of Rabies in Bali in the Year of 2014 - Wisnu Adi Saputra, IGNA; Dibia, I Nyoman; Puja, I Ketut (Veterinary Science and Medicine Journal; Vol 3 No 2 (2015), 2015)
The aims of this study was to determine the spatial distribution and the risk factors associated with theincidence of rabies in Bali on the year of 2014. A total of 1286 brain samples from all over the Bali wasexamined.  Out of  all brain samples, 130 samples were diagnosed positive for rabies. Based on these data,we collected the dogs location coordinates using a tool of Global Positioning System (GPS). Thosecoordinates  were, then, analyzed with GIS software. The results showed that spatial distribution of theincidence of rabies in each regencies in Bali varied, however, it had a same pattern. The factors ofcounseling, breed, trade, and geographical condition associated to the incidence of rabies. Further researchis needed to map the incidence of rabies over a longer time (more than 3 years), to improve theeffectiveness of surveillance in connection with the eradication of rabies in Bali.
Keywords: rabies, risk factors, spatial distribution, GIS